Adolescent Spinal Pain-Related Absenteeism as an Antecedent for Early Adulthood Work Presenteeism. Issue 12 (December 2020) - Beales, Darren; Coenen, Pieter; Smith, Anne; Harris, Mark; Pransky, Glenn; O'Sullivan, Peter; Straker, Leon
Abstract : Objectives: This study investigated spinal pain-related absenteeism at age 17 as a potential precursor to work presenteeism at age 23. Methods: A longitudinal study was performed with Raine Study Gen2 participants ( n = 451). Spinal pain-related absenteeism from school/work was collected at the 17 year follow-up. Presenteeism (due to ill-health or any other reason) was collected quarterly during one year around the age of 23. Zero-inflated binominal regression analysis was conducted. Results: Participants with adolescent spinal pain-related absenteeism reported higher work presenteeism in early adulthood than those without pain (155.7 h/y compared to 77.7 h/y), with an incident rate ratio (95% confidence interval) of 1.41 (1.04 to 1.92) after adjusting for sex, occupational class and multimorbidity count. Conclusions: Targeting factors associated with absenteeism behaviours during early life may have significant benefits for future work productivity. Abstract : Supplemental Digital Content is available in the text